An epigenetically mediated double negative cascade from EFD to HB21 regulates anther development - Zhang, Cheng; Xiong, Ao-Tong; Ren, Meng-Yi; Zhao, Yan-Yun; Huang, Min-Jia; Huang, Long-Cheng; Zhang, Zheng; Wang, Yun; Zheng, Quan-Quan; Fan, Jing; Guan, Jing-Jing; Yang, Zhong-Nan (Nature communications, 2024)
Epigenetic modifications are crucial for plant development. EFD ( E xine F ormation D efect) encodes a SAM-dependent methyltransferase that is essential for the pollen wall pattern formation and male fertility in Arabidopsis. In this study, we find that the expression of DRM2 , a de novo DNA methyltransferase in plants, complements for the defects in efd , suggesting its potential de novo DNA methyltransferase activity. Genetic analysis indicates that EFD functions through HB21 , as the knockout of HB21 fully restores fertility in efd mutants. DNA methylation and histone modification analyses reveal that EFD represses the transcription of HB21 through epigenetic mechanisms. Additionally, we demonstrate that HB21 directly represses the expression of genes crucial for pollen formation and anther dehiscence, including CalS5 , RPG1/SWEET8 , CYP703A2 and NST2 . Collectively, our findings unveil a double negative regulatory cascade mediated by epigenetic modifications that coordinates anther development, offering insights into the epigenetic regulation of this process. Epigenetic modifications are crucial for plant development. Here, the authors find an epigenetically mediated double negative cascade for pollen formation and anther dehiscence, offering new insights into epigenetic regulation of anther development.